1999
DOI: 10.1046/j.1365-2648.1999.01087.x
|View full text |Cite
|
Sign up to set email alerts
|

Chinese elderly patients’ perceptions of their rehabilitation needs following a stroke

Abstract: Stroke is the third leading cause of death and disability among Chinese elderly patients in Hong Kong and yet the rehabilitation needs of these patients are rarely explored. The aim of this study was to identify the rehabilitation needs of Chinese elderly patients following a stroke. The study adopted an ethnographic approach, information being gathered by the researcher through interviews with 15 key informants selected by purposive sampling. The perceptions of patients as to their own needs were sought at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 16 publications
4
55
0
Order By: Relevance
“…Indeed, previous local studies have identi ed Chinese elderly people's preferred sources of assistance when they were in need of help. In identifying the rehabilitation needs of elders after a stroke, Lui & Mackenzie (1999) found that Chinese elders were very reserved about seeking help from people whom they considered to be 'outside the family'. Moreover, residential home staff are seen as people who make up and administer the 'laws' of the home, they are the authority gures in the home.…”
Section: Relations With Other Residents and Staffmentioning
confidence: 99%
“…Indeed, previous local studies have identi ed Chinese elderly people's preferred sources of assistance when they were in need of help. In identifying the rehabilitation needs of elders after a stroke, Lui & Mackenzie (1999) found that Chinese elders were very reserved about seeking help from people whom they considered to be 'outside the family'. Moreover, residential home staff are seen as people who make up and administer the 'laws' of the home, they are the authority gures in the home.…”
Section: Relations With Other Residents and Staffmentioning
confidence: 99%
“…These were reported as psychosocial, social, and spiritual as well as physical dimensions of need. 42 One study reported patients' accounts of the difficulties they face eating, and the fear and shame this and their changed physical and social appearance created for them. 43 Patients assessed as needing adaptive aids were found to be sometimes reluctant to use such devices because they reinforced the sense of loss associated with stroke impairment.…”
Section: Rehabilitation Therapiesmentioning
confidence: 99%
“…Information related to the longitudinal needs of people with stroke could help hospital-and communitybased therapists to more effectively plan physiotherapy service beyond the initial period of returning home. Previous studies [3][4][5][6][7][8][9][10][11] have also tended to present patients with stroke as a relatively homogeneous group. It seems reasonable to expect, however, that the needs of people with mild stroke impairment will differ from those of people with more severe impairment and limited function.…”
mentioning
confidence: 99%